Redesign of Plastic Waste Processing Facility Layout at PT Inastek Using Computerized Relationship Layout Planning (Corelap) Method - Aura Diva Shafa Dharma; Rusindiyanto Rusindiyanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
Factory layout is the main foundation of the industrial world. A well-planned factory layout will help determine the efficiency and effectiveness of production activities and in some cases will also maintain the survival or success of a company. Based on the results of field observations and interviews that have been conducted, the problem faced by the company is the arrangement of the production floor layout that has poor flow, including workstations that have a relationship of material flow sequences that are placed far apart. This causes a lot of land area used and high OMH costs. One of the proposed methods that can be used to solve this problem is the Computerized Relationship Layout Planning (CORELAP) method. The CORELAP method was chosen to improve the facility's layout by producing a minimum material movement distance. In addition, this method allows for maximum area utilization, higher production capacity, and a more regular production flow. The total distance in the old layout is 39.25 meters and the new layout is 26.75, proving that the distance traveled by the proposed layout is more minimal meets the requirements of a proposed layout, and can reduce the company's OMH value.